2019
DOI: 10.1016/s2468-2667(19)30002-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in child maltreatment in England and Wales, 1858–2016: an observational, time-series analysis

Abstract: Background It is unclear whether child maltreatment is increasing or decreasing in England and Wales. More evidence is needed, from multiple sources and over longer periods of time, to explore trends in child maltreatment. We investigated whether the annual incidence of child maltreatment has changed over time, using official record data and time-series methods to establish long-term trends. Methods In this observational time-series analysis, we used six data sources (Government records for child mortality, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…The study found a decreasing long-term trend in child maltreatment until the year 2000 but reported an increase thereafter. 30 However, child mortality continued to decrease. 30 A recommendation of the report was to further research and establish whether child maltreatment is continuing to increase.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found a decreasing long-term trend in child maltreatment until the year 2000 but reported an increase thereafter. 30 However, child mortality continued to decrease. 30 A recommendation of the report was to further research and establish whether child maltreatment is continuing to increase.…”
Section: Open Accessmentioning
confidence: 99%
“…30 However, child mortality continued to decrease. 30 A recommendation of the report was to further research and establish whether child maltreatment is continuing to increase. 30 However, once again when taken from the CSEW, the estimated prevalence of experiencing childhood maltreatment was 18.9% (financial year end 2016).…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies enable the authors to arrive at several novel findings. 5 First, fatal violence against children in England and Wales has steadily decreased for the past 150 years (90% decrease in child death by homicide or assault between 1858 and 2016); this trend is most prominent among children younger than 1 year. Second, in the 21st century, registrations with child protection services have proliferated (182% increase between 1988 and 2016), driven increasingly by neglect and emotional abuse rather than physical abuse.…”
Section: Administrative Data and Long-term Trends In Child Maltreatmementioning
confidence: 99%
“…As the rapid digitisation of historical data opens exciting new frontiers in research, it will be important to remember the consequences of missing data and to compare like for like when analysing trends. Through the innovative use of multiple sources of administrative data, Esposti and colleagues 5 generate some definitive conclusions about long-term decreases in severe violence against children. If their findings about trends since the turn of the century are less conclusive, their approach nevertheless charts a careful path for navigating the thorny problem of measuring trends in child abuse and neglect, a path that others should emulate.…”
Section: Administrative Data and Long-term Trends In Child Maltreatmementioning
confidence: 99%